Key Problems in Bolivian Education System - Jírů, Lucie (2025)
This diploma thesis aims to identify the key challenges related to the quality of education and inequalities in access to primary and secondary schooling within Bolivia’s Subsystem of Regular Education. The work covers the period 2000–2024 applying a case study approach to analyse quantitative data and connects findings with existing research. Despite progress in enrolment and gender parity, significant inequalities persist. At the secondary level, students in rural areas continue to have lower enrolment, attendance, and completion rates. Additionally, indigenous students face further challenges, including social barriers and limited access to bilingual instruction. Learning outcomes remain low in reading comprehension, math and science with rural and indigenous students most affected due to uneven teacher distribution and insufficiently targeted investments. Overall, although Bolivia allocates a high share of national resources to education, this spending does not translate into better access or higher learning quality, revealing persistent structural inequalities.